Savings and Investment Behaviour of Beedi Rollers – A Quantitative ABCD Analysis - Harinakshi; Narayan Kayarkatte, (International Journal of Management, Technology and Social Sciences (IJMTS), 2023)
Purpose: The main goal of this study is to use the comprehensive ABCD analysis approach to analyse beedi rollers' savings and investment behaviour. In order to understand the subject matter better, the study also intends to use factor analysis and elementary analysis. Design: The study technique includes an ABCD framework-based basic analysis as well as a systematic examination of the literature using keyword searches that target specific factors. The focus group method is used to conduct quantitative analysis, and the study's identified factors and components are given different weights. Findings: The findings of the researcher illustrate the ABCD framework's appropriateness for a wide range of research endeavours, including the current study. The evidence gathered from the focus group interviews clearly indicates the significant benefits of examining the specific topic under consideration. Originality value: This study offers insightful information by expanding the application of the ABCD analysis paradigm to the setting of savings and investment behaviour among beedi rollers. This study leads research in the area of savings and investment behaviour by identifying critical constituent issues and stressing their significance in this particular context. Paper Type: Empirical Analysis